Financial Development and Economic Growth - Guidotti, Pablo (IMF Working Papers; Working Paper, 1992)
This paper examines the empirical relationship between long-run growth and the degree of financial development, proxied by the ratio of bank credit to the private sector as a fraction of GDP. We find that this proxy enters significantly and with a positive sign in growth regressions on a large cross-country sample, but with a negative sign using panel data for Latin America. Our findings suggest that the main channel of transmission from financial development to growth is the efficiency of investment, rather than its volume. We also present a model where the negative correlation between financial intermediation and growth results from financial liberalization in a poor regulatory environment.